Mitochondria-targeted therapy with metformin and MitoQ reduces oxidative stress, improves mitochondrial function, and restores metabolic homeostasis in a murine model of Gulf War Illness - Lun Cai; Mundanattu Swetha; Abraham Raji; Alvin V. Terry, Jr.; Raghavan Pillai Raju (Redox Biology)
Gulf War Illness (GWI) is a cluster of medically unexplained chronic symptoms, including neurological and gastrointestinal impairments, and muscle fatigue, suffered by veterans of the Persian Gulf War. A GWI model in C57BL/6 mice exposed to the nerve gas prophylactic pyridostigmine-bromide (PB) and the insecticide permethrin (PER) was used to test the effect of mitochondria-potentiating agents, metformin and MitoQ on chronic fatigue, observed in GWI. The exposure of mice to PB/PER resulted in enhanced oxidative stress, impaired mitochondrial function, and reduced autophagy. Treatment with the anti-diabetic drug metformin and the mitochondria-targeted antioxidant available as a dietary supplement, MitoQ, activated the AMPK signaling, reduced oxidative stress, and attenuated inflammation in gastrocnemius muscle tissue compared to untreated mice. The combination of metformin and MitoQ was found to be more effective than the individual treatments in activating AMPK. The combination treatment rescued autophagy and improved mitochondrial respiration. Chronic fatigue assessments by the hanging wire and rotarod tests, and voluntary wheel running activities showed improved physical activity/strength in mice treated with metformin and MitoQ. The results suggest the potential therapeutic benefit of a combination formulation of metformin and MitoQ in addressing the molecular and energetic impairments of skeletal muscle in GWI.